The impact of decentralisation policy on small business in Indonesia: a study of politics in Bantul District, Yogyakarta and Gianyar District, Bali - Subarsono, Agustinus (Curtin University, 2012)
The objective of this study is to analyse the impact of decentralisation on the relationship between local governments and small businesses in Bantul and Gianyar.This study found that district governments cannot use regulations to control small businesses. The Bantul district head more intensively promotes small businesses than the Gianyar district. Decentralisation cannot encourage politicians to be close to small businesses. In Bantul, political parties develop networks with business associations but neither in Gianyar.